Beispiel Nr: 22
$ \text{Gegeben:} \\ a1 \cdot x +b1 \cdot y =c1\\ a2 \cdot x +b2 \cdot y =c2 \\ \\ \text{Gesucht:} \\\text{x und y} \\ \\ \textbf{Gegeben:} \\ \\ -7 x +9 y =-3\\ 5 x -6 y = -4 \\ \\ \\ \\ \textbf{Rechnung:} \\\begin{array}{l|l} \begin{array}{l} I \qquad -7 x +9 y =-3\\ II \qquad 5 x -6 y = -4 \\ \text{I nach y auflösen}\\ -7 x +9 y =-3 \\ -7 x +9 y =-3 \qquad /+7 x\\ 9 y =-3 +7 x \qquad /:9 \\ y =-\frac{1}{3} +\frac{7}{9} x \\ \text{II nach y auflösen}\\ 5 x -6 y =-4 \\ 5 x -6 y =-4 \qquad /-5 x\\ -6 y =-4 -5 x \qquad /:\left(-6\right) \\ y =\frac{2}{3} +\frac{5}{6} x \\ \text{I = II}\\ -\frac{1}{3} +\frac{7}{9} x =\frac{2}{3} +\frac{5}{6} x \qquad /-\frac{7}{9} x /-\frac{2}{3} \\ -\frac{1}{3}-\frac{2}{3} =\frac{5}{6} x -\frac{7}{9} x \\ -1 =\frac{1}{18} x \qquad /:\frac{1}{18} \\ x=-18 \\ \text{x in I}\\ y =-\frac{1}{3} +\frac{7}{9} \cdot -18 \\ y=-14\frac{1}{3} \\ L=\{-18/-14\frac{1}{3}\} \end{array} & \begin{array}{l} I \qquad -7 x +9 y =-3\\ II \qquad 5 x -6 y = -4 \\ \text{I nach x auflösen}\\ -7 x +9 y =-3 \\ -7 x +9 y =-3 \qquad /-9 y\\ -7 x =-3 -9 y \qquad /:\left(-7\right) \\ x =\frac{3}{7} +1\frac{2}{7} y \\ \text{II nach x auflösen}\\ 5 x -6 y =-4 \\ 5 x -6 y =-4 \qquad /+6 y\\ 5 x =-4 +6 y \qquad /:5 \\ x =-\frac{4}{5} +1\frac{1}{5} y \\ \text{I = II}\\ \frac{3}{7} +1\frac{2}{7} y =-\frac{4}{5} +1\frac{1}{5} y \qquad /-1\frac{2}{7} y /+\frac{4}{5} \\ \frac{3}{7}+\frac{4}{5} =1\frac{1}{5} y -1\frac{2}{7} y \\ 1\frac{8}{35} =-\frac{3}{35} y \qquad /:\left(-\frac{3}{35}\right) \\ y=-14\frac{1}{3} \\ \text{y in I}\\ x =\frac{3}{7} +1\frac{2}{7} \cdot -14\frac{1}{3} \\ x=-18 \\ L=\{-18/-14\frac{1}{3}\} \end{array} \end{array} $